Supercritical ethanol as an enhanced medium for lignocellulosic biomass liquefaction: Influence of physical process parameters - Brand, Steffen; Susanti, Ratna Frida; Kim, Seok Ki; Lee, Hong-shik; Kim, Jaehoon; Sang, Byung-In (Energy (Oxford), 2013)
In this study, the influence of various physical process parameters on the liquefaction of lignocellulosic biomass (pine wood) in supercritical ethanol was investigated. The parameters include reaction temperature (280–400 °C), initial nitrogen pressure (0.4–7.5 MPa), reaction time (0–240 min), and biomass-to-solvent ratio (0.06–0.25 g/g). The reaction temperature and residence time were found to have a more significant effect on biomass conversion and product yield than pressure and biomass-to-solvent ratio had; conversion in the range 34.0–98.1% and biocrude yield in the range 15.8–59.9 wt% were observed depending on the process parameters. Despite the absence of catalysts and external hydrogen source, solid biomass to liquid and gaseous products conversion of 98.1%, and a high biocrude yield of approximately 65.8 wt% were achieved at 400 °C, 120 min, and a biomass-to-solvent ratio of 0.06 g/g. Moreover, the biocrude contained considerably lower amounts of oxygen and higher amounts of carbon and hydrogen, resulting in a substantially higher heating value (>30 MJ/kg) as compared to raw feedstock (20.4 MJ/kg). A comparison with sub- or supercritical water-based liquefaction revealed that supercritical ethanol produced biocrude with a lower molecular weight and much better yield. Finally, a new biomass liquefaction reaction mechanism associated with supercritical ethanol is proposed. •Influence of physical parameters on biomass liquefaction in supercritical ethanol.•Benefits of supercritical ethanol as a solvent in biomass liquefaction.•High conversion (98%) and high biocrude yield (66 wt%) achieved.•Comparison with sub- and supercritical water liquefaction has been made.•New reaction mechanism of supercritical alcohol has been proposed.